2005
DOI: 10.1142/s0218957705001527
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Carpal Tunnel Compliance

Abstract: The purposes of this study were to investigate the mechanical properties of the carpal tunnel and to examine carpal tunnel compliance as it related to gender difference. Twelve male and twelve female subjects without any neuromusculoskeletal disorders in the upper extremities participated in the study. Indentation testing was manually performed on the wrist volar to the transverse carpal ligament. Effective compliance was defined as the slope of the regression analyses of indentation force and displacement dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
2
20
1
Order By: Relevance
“…However, indentation is the most common method of evaluating TCL behavior, so it is an important benchmark. The average TCL stiffness in this work (28.0N/mm–non-muscle attachment and 9.7N/mm–muscle attachment sites) was in the same general range as the TCL stiffness that has been measured by in vivo indentation (9.9N/mm for males and 13.3N/mm for females) (Li, 2005). The slight variation may be a result of the fact that the Li 2005 indentation study included compression of the skin and other presumably softer tissues overlying the TCL (muscle, fat, etc.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, indentation is the most common method of evaluating TCL behavior, so it is an important benchmark. The average TCL stiffness in this work (28.0N/mm–non-muscle attachment and 9.7N/mm–muscle attachment sites) was in the same general range as the TCL stiffness that has been measured by in vivo indentation (9.9N/mm for males and 13.3N/mm for females) (Li, 2005). The slight variation may be a result of the fact that the Li 2005 indentation study included compression of the skin and other presumably softer tissues overlying the TCL (muscle, fat, etc.…”
Section: Discussionsupporting
confidence: 75%
“…Numerous studies have investigated overall compliance of the carpal tunnel complex (Li, 2005; Tung et al, 2010; Zheng et al, 2006) and the TCL’s role in maintaining carpal bone stability (Garcia-Elias et al, 1989; Guo et al, 2009; Li et al, 2009; Tengrootenhuysen et al, 2009; Xiu et al, 2010). However, only a few studies have isolated the TCL and assessed its intrinsic properties.…”
Section: Introductionmentioning
confidence: 99%
“…A factor to consider is the structural mechanics of the carpal tunnel because a relatively rigid carpal tunnel is needed for pressure elevation to occur. 13 Previous studies have examined the compliance of carpal tunnel between males and females 14 or among humans and various animals determining that the human carpal tunnel was the least compliant. 13 Another compliance study examined the influence of carpal tunnel pressure on carpal tunnel morphology and found that as carpal tunnel pressure increased, the carpal tunnel area increased and the cross-sectional shape of the carpal tunnel became rounder.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the direction of the maximum principal stiffness is also associated with functional wrist kinematics related to dart throwing motion (Capener, 1956; Fisk, 1981; Garcia-Elias, 2013; Li, 2005; Moritomo et al, 2007; Palmer et al, 1985; Werner et al, 2004). Dart throwing motion refers to the most common wrist motion, from radial-extension to ulnar-flexion, that occurs during various functional tasks of the hand such as swinging a hammer (Capener, 1956; Fisk, 1981; Garcia-Elias, 2013; Li, 2005; Moritomo et al, 2007; Palmer et al, 1985; Werner et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Dart throwing motion refers to the most common wrist motion, from radial-extension to ulnar-flexion, that occurs during various functional tasks of the hand such as swinging a hammer (Capener, 1956; Fisk, 1981; Garcia-Elias, 2013; Li, 2005; Moritomo et al, 2007; Palmer et al, 1985; Werner et al, 2004). The maximum principal stiffness direction is aligned with the rotational axis of dart throwing motion.…”
Section: Discussionmentioning
confidence: 99%